2022
DOI: 10.3389/frph.2022.927211
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual changes after COVID-19 vaccination and/or SARS-CoV-2 infection and their demographic, mood, and lifestyle determinants in Arab women of childbearing age, 2021

Abstract: BackgroundBy September 2, 2021, over 30,000 COVID-19-vaccinated females had reported menstrual changes to the MHRA's Yellow Card surveillance system. As a result, the National Institutes of Health (NIH) is urging researchers to investigate the COVID-19 vaccine's effects on menstruation. Therefore, this study was conducted to explore the menstrual changes after COVID-19 vaccination and/or SARS-CoV-2 infection and their interrelations with demographic, mood, and lifestyle factors in Arab women of childbearing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
2
19
2
3
Order By: Relevance
“…A higher prevalence of menstrual abnormalities among Pfizer recipients compared to AstraZeneca recipients was also observed among Arab women (49.3 vs . 21.1%) 33 . The reporting rates based on the spontaneous reports from our study, however, showed that the Johnson & Johnson vaccine had the highest reporting rates compared to the other vaccine brands: overall, 523.0 reports of menstrual abnormalities per 100 000 administered vaccines.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A higher prevalence of menstrual abnormalities among Pfizer recipients compared to AstraZeneca recipients was also observed among Arab women (49.3 vs . 21.1%) 33 . The reporting rates based on the spontaneous reports from our study, however, showed that the Johnson & Johnson vaccine had the highest reporting rates compared to the other vaccine brands: overall, 523.0 reports of menstrual abnormalities per 100 000 administered vaccines.…”
Section: Discussioncontrasting
confidence: 56%
“…A higher prevalence of menstrual abnormalities among Pfizer recipients compared to AstraZeneca recipients was also observed among Arab women (49.3 vs. 21.1%). 33 The reporting rates based on the spontaneous reports from our study, however, showed Several studies have examined the effect of COVID-19 vaccination on the menstrual cycle (length) and/or menses. 25,34 Nazir et al summarized the methodological aspects and main outcomes of 14 studies in a systematic review, most of which had a cross-sectional design.…”
Section: Use Of Contraceptivesmentioning
confidence: 61%
“…in Arab countries, menstrual cycle changes after COVID-19 vaccinations were highly associated with sociodemographic variable such as age, marital status, level of education, nationality, and others. 28 On top of that, we found that women who had fibroids reported a higher incidence of menstrual cycle changes. In a systematic review conducted by Nazir et al, existing gynecological problems such as endometriosis, fibroids, and adenomyosis were linked to an increase in the incidence of menstrual changes following vaccination.…”
Section: Discussionmentioning
confidence: 79%
“…Weitere Forschungsgruppen haben sich bereits mit diesem Thema auseinandergesetzt. Es stellte sich heraus, dass von 524 Frauen nach einer COVID-19-Erkrankung rund 19 % Veränderungen der Menstruation hatten, wobei knapp die Hälfte dieser aus Hypomenorrhö bestand [ 27 ]. In einer globalen Fragebogenstudie der Patient-Led Research Collaborative (einer Gruppe an Personen, die selbst an Long COVID leiden) zeigte sich bei circa 5 % der teilnehmenden Frauen eine Frühmenopause, während weitere 5 % von Zwischenblutungen berichteten, obwohl sie bereits nach der Menopause waren [ 28 ].…”
Section: Long Covid Und Menstruationsveränderungenunclassified